The Influence of the Educational Environment and Parenting Patterns on Children's Growth and Development in the New Normal Era after Covid 19 in the Playgroup of Babadan District, Ponorogo Regency, Indonesia. - Jauhan Budiwan; Abdah Munfaridatus Sholihah (Lighthouse Publishing, 2022)
The covid-19 outbreak has changed the educational structure and psychology of child development, the role of teachers, parents and the environment is needed for good development. In the new normal era after covid 19, what is the paradigm model in children's education. This article aims to determine the influence of the educational environment and parenting patterns on children's growth and development in the new normal era after covid 19 in the Babadan sub-district playgroup, Ponorogo district. This research is a field study where to measure the influence of the environment and parents on children's growth and development in the new normal era after covid 19 in the Babadan Subdistrict Playgroup, Ponorogo Regency by using the bivariate correlation test in three schools, namely the Al-Islam playgroup, the Permata Hati playgroup and the Aisiyahplaygroup. The results showed that there was no influence between the role of the environment and parents on the growth and development of children in the post-covid 19 era in two schools, namely the Al-Islam playgroup and the Permata Hati playgroup. Meanwhile, in Aisyiyah's playgroup there is a significant influence on the role of the environment and parents on children's growth and development.